Aberrant phenotype of circulating antigen presenting cells in giant cell arteritis and polymyalgia rheumatica - Reitsema, Rosanne D.; Hesselink, Bernd-Cornèl; Abdulahad, Wayel H.; van der Geest, Kornelis S. M.; Brouwer, Elisabeth; Heeringa, Peter; van Sleen, Yannick (Frontiers in Immunology, 2023)
Background: Giant Cell Arteritis (GCA) and Polymyalgia Rheumatica (PMR) are overlapping inflammatory diseases. Antigen-presenting cells (APCs), including monocytes and dendritic cells (DCs), are main contributors to the immunopathology of GCA and PMR. However, little is known about APC phenotypes in the peripheral blood at the time of GCA/PMR diagnosis.Methods: APCs among peripheral blood mononuclear cells (PBMCs) of treatment-naive GCA and PMR patients were compared to those in age-and sex-matched healthy controls (HCs) using flow cytometry (n=15 in each group). We identified three monocyte subsets, and three DC subsets: plasmacytoid DCs (pDCs), CD141+ conventional DCs (cDC1) and CD1c+ conventional DCs (cDC2). Each of these subsets was analyzed for expression of pattern recognition receptors (TLR2, TLR4), immune checkpoints (CD86, PDL1, CD40) and activation markers (HLA-DR, CD11c).Results: t-SNE plots revealed a differential clustering of APCs between GCA/PMR and HCs. Further analyses showed shifts in monocyte subsets and a lower proportion of the small population of cDC1 cells in GCA/PMR, whereas cDC2 proportions correlated negatively with CRP (r=-0.52). Classical monocytes of GCA/PMR patients show reduced expression of TLR2, HLA-DR, CD11c, which was in contrast to non-classical monocytes that showed higher marker expression. Additionally, single cell RNA sequencing in GCA patients identified a number of differentially expressed genes related to inflammation and metabolism in APCs. This is a provisional file, not the final typeset article Conclusion: Circulating non-classical monocytes display an activated phenotype in GCA/PMR patients at diagnosis, whereas classical monocytes show reduced expression of activation markers. Whether these findings reflect APC migration patterns or the effects of long-term inflammation remains to be investigated.